RETRACTED: Creating an original technique for identifying objects in video streams - Alexandrov Islam; Ruslantsev Andrei; Aslanov Tagirbek; Gorelov Viktor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001